2006
DOI: 10.1002/bit.20940
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of labeled and native protein in confocal laser scanning microscopy

Abstract: Confocal laser scanning microscopy has been previously applied to the study of protein uptake in porous chromatography resins. This method requires labeling the protein with a fluorescent probe. The labeled protein is then diluted with a large quantity of native protein so that the fluorescence intensity is a linear function of the labeled protein concentration. Ideally, the attachment of a fluorescent probe should not affect the affinity of the protein for the stationary phase; however, recent experimental wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Liapis et al [22] and Zhang et al [23] included an additional contribution to the transport equations from a double-layer-induced electrophoretic transport mechanism. Recently, other workers have proposed that the overshoot is caused by the displacement of weaker-binding fluorescently labelled protein by its stronger-binding unlabelled native counterpart [10,12,13,24].…”
Section: Single-component Adsorptionmentioning
confidence: 98%
“…Liapis et al [22] and Zhang et al [23] included an additional contribution to the transport equations from a double-layer-induced electrophoretic transport mechanism. Recently, other workers have proposed that the overshoot is caused by the displacement of weaker-binding fluorescently labelled protein by its stronger-binding unlabelled native counterpart [10,12,13,24].…”
Section: Single-component Adsorptionmentioning
confidence: 98%
“…For example, early studies that applied CLSM to ion-exchange chromatography revealed the existence of an unexpected concentration 'overshoot' phenomenon (Dziennik et al, 2003;Hubbuch et al, 2002Hubbuch et al, , 2003, which initially was attributed to a novel non-diffusive protein transport mechanism (Dziennik et al, 2003;Liapis et al, 2001). Recent experimental and modeling studies have, however, cast doubt upon these early interpretations by revealing how protein displacement during competitive adsorption can explain the obtained intraparticle concentration profiles (Martin et al, 2005;Teske et al, 2005Teske et al, , 2006. Experimentally, bio-conjugates are diluted with a high fraction of the native protein species in order to ensure signal linearity.…”
Section: Introductionmentioning
confidence: 96%
“…2). The latter has been shown to have significant effects when considering the influence of the attached dye on the adsorption and transport behavior of the protein-dye conjugate especially for ion exchange processes [15,18,19,25,34]. In addition to the alteration of long-range electrostatic interactions, hydrophobic alterations of the surface may also play an important role but was not analyzed so far comprehensively for the majority of commercially available dyes.…”
Section: Dye Propertiesmentioning
confidence: 95%